Three cases with Klippel-Trenaunay syndrome and treatment options - Çelik, Ersin; Alat, İlker (The European Research Journal, 2020)
Klippel-Trenaunay syndrome (KTS) is a rare congenital anomaly characterized by capillary malformations, soft tissue and bone hypertrophy and varicosities. The presence of at least two of the three clinical conditions is sufficient for the diagnosis of KTS. Early diagnosis and treatment are important because of possible serious complications such as deep vein thrombosis and pulmonary embolism. Venous system aplasia and/or hypoplasia might be observed in KTS. Therefore, deep venous system must be evaluated definitely before determining the treatment strategy. It's herein presented our conservative and surgical treatment applications in three KTS patients.